A Rapidly Evolving Polybasic Motif Modulates Bacterial Detection by Guanylate Binding Proteins - Kristin M. Kohler (American Society for Microbiology, 2020)
ABSTRACT Cell-autonomous immunity relies on the rapid detection of invasive pathogens by host proteins. Guanylate binding proteins (GBPs) have emerged as key mediators of vertebrate immune defense through their ability to recognize a diverse array of intracellular pathogens and pathogen-containing cellular compartments. Human and mouse GBPs have been shown to target distinct groups of microbes, although the molecular determinants of pathogen specificity remain unclear. We show that rapid diversification of a C-terminal polybasic motif (PBM) in primate GBPs controls recognition of the model cytosolic bacterial pathogen Shigella flexneri. By swapping this membrane-binding motif between primate GBP orthologs, we found that the ability to target S. flexneri has been enhanced and lost in specific lineages of New World primates. Single substitutions in rapidly evolving sites of the GBP1 PBM are sufficient to abolish or restore bacterial detection abilities, illustrating a role for epistasis in the evolution of pathogen recognition. We further demonstrate that the squirrel monkey GBP2 C-terminal domain recently gained the ability to target S. flexneri through a stepwise process of convergent evolution. These findings reveal a mechanism by which accelerated evolution of a PBM shifts GBP target specificity and aid in resolving the molecular basis of GBP function in cell-autonomous immune defense. IMPORTANCE Many infectious diseases are caused by microbes that enter and survive within host cells. Guanylate binding proteins (GBPs) are a group of immune proteins which recognize and inhibit a variety of intracellular pathogenic microbes. We discovered that a short sequence within GBPs required for the detection of bacteria, the polybasic motif (PBM), has been rapidly evolving between primate species. By swapping PBMs between primate GBP1 genes, we were able to show that specific sequences can both reduce and improve the ability of GBP1 to target intracellular bacteria. We also show that the ability to envelop bacteria has independently evolved in GBP2 of South American monkeys. Taking the results together, this report illustrates how primate GBPs have adapted to defend against infectious pathogens.